PERTANGGUNGJAWABAN PIDANA KORPORASI PADA PERKARA TINDAK PIDANA PENCUCIAN UANG - Listawati Listawati (Penerbit Universitas Atma Jaya Yogyakarta, 2021)
Law Number 8 Year 2010 concerning Prevention and Eradication of Money Laundering Act (UU TPPU) has stipulates that criminal liability shall not only apply to natural persons but also legal entities and non-legal entities. In practice, corporate criminal liability has only been applied in the case of money laundering crimes committed by PT. Beringin Bangun Utama. This paper is intended to determine the regulation of corporate criminal liability based on the Money Laundering Law and its application in the case of PT. Beringin Bangun Utama. This study uses a normative method with 3 (three) approaches, namely the statutory approach, the case approach, and the conceptual approach. The results of the research conclude that corporate criminal liability in money laundering cases uses the doctrine of identification where to be able to impose criminal responsibility on corporations, law enforcement must be able to identify that those who commit (actus reus) are controlling personnel (directing mind or controlling mind). Furthermore, the intention or the attitude of the heart of guilt (mens rea) in the the doctrine of identification can be determined if the crime is committed in the context of providing benefits to the corporation.